2000
DOI: 10.1038/sj.jhh.1000942
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Gly460Trp polymorphism of the α-adducin gene in primary hypertension in Scandinavians

Abstract: Previous studies have suggested that the Trp460 allele of the Gly460Trp polymorphism in the ␣-adducin gene is associated with salt sensitivity and primary hypertension. The present study was undertaken to evaluate if the Trp460 allele of this polymorphism is associated with primary hypertension in Scandinavians. To address this issue, 294 patients with primary hypertension and 265 normotensive control subjects from Sweden were examined and genotyped for the Gly460Trp polymorphism using polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
(30 reference statements)
1
21
0
2
Order By: Relevance
“…They found evidence that ␣-adducin gene polymorphism is associated with some cases of essential hypertension in man, with plasma renin activity being lower in the predisposed subjects. 209 The findings have been supported by some, 211,212 but not all, [213][214][215][216] other workers.…”
Section: Genetic Aspectssupporting
confidence: 71%
“…They found evidence that ␣-adducin gene polymorphism is associated with some cases of essential hypertension in man, with plasma renin activity being lower in the predisposed subjects. 209 The findings have been supported by some, 211,212 but not all, [213][214][215][216] other workers.…”
Section: Genetic Aspectssupporting
confidence: 71%
“…In 10 populations, a positive association was found (10,13,32,42,80,116,119,124,156), whereas in two populations, a positive association was found only in women (128) or young subjects (132). In 13 populations, no association was present (2,3,38,70,74,79,84,88,100,116,119,124,151). In three studies (116,119,124), both positive and negative associations are observed in different populations.…”
Section: Studies In Humansmentioning
confidence: 86%
“…20 Two subjects from the previous study 20 were excluded because of unsuccessful genotyping. Briefly, the patients with primary hypertension were diagnosed before the age of 60 years and were all receiving chronic pharmacological antihypertensive treatment.…”
Section: Subjects and Phenotypingmentioning
confidence: 99%